UJI DAYA HAMBAT SERBUK DAUN KAYU MANIS (Cinnamomum burmanii) TERHADAP BAKTERI Streptococcus agalactiae - Eka Yunita Wulandari; Endah Sri Redjeki; Firma Fika Rahmawati (Universitas Muhammadiyah Gresik, 2018)
Streptococcus agalactiaeis a bacterium that causes Streptococcosis in tilapia (Oreochromisniloticus). Antibioticis being used efforts to control the disease. Using antibiotics constantly willadversely affect the aquatic environment, bacterial resistance and presence of residues in fishconsumption. Another alternative is to use phytopharmaca materials that are natural andenvironmentally friendly. One of the phytopharmaca materials that can be used is cinnamon(Cinnamomum burmanii) which contains active ingredients such as Saponin, Alkanoid, Tanin,Flavanoid, Sinamaldehid. The purpose of this study was to investigates the effectiveness and thebest dose of cinnamon leaves (C. burmanii) as an antibacterial agent for the prevention of S.agalactiaeinfection. This research was experimental desion was group randomized design (GRD)3 treatments and 3replicationswere used treatments that is A (concentration 0,25%), B(concentration 0,5%), C (concentration 1%), K (control). Test this study by calculating thenumber of colonies grown on agar medium. The result showed that B treatment (0.5%concentration) can inhibit S. agalactiae bacteria growth with marked growth of bacteria on TSA(Trypticase soyaagar) medium.